2006 IEEE International Technology Management Conference (ICE) 2006
DOI: 10.1109/ice.2006.7477083
|View full text |Cite
|
Sign up to set email alerts
|

RFID in automotive: A Closed-Loop approach

Abstract: Every year more than 10 million vehicles reach the end of their useful life in the European Union and generate more than 9 million tons of waste. The European Union issued the directive 2000/53/EC in 2000 aimed at reducing pollution and waste of resources generated by such a huge amount of end of life vehicles (EL V s). Car manufacturers and the other EL V s economic operators actually are working together in order to fulfil EU EL V s directive targets but meeting EU standards will become more difficult in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…When combining the usage information with a value estimate, it becomes possible to calculate a residual value of each part and make an even more ne-grained decision of what is the most appropriate action to take for each part. Such possibilities could enable new recycling and refurbishing business opportunities as in the automotive industry [43] or for heavy machinery as identied by Caterpillar [20].…”
Section: End-of-life Managementmentioning
confidence: 99%
“…When combining the usage information with a value estimate, it becomes possible to calculate a residual value of each part and make an even more ne-grained decision of what is the most appropriate action to take for each part. Such possibilities could enable new recycling and refurbishing business opportunities as in the automotive industry [43] or for heavy machinery as identied by Caterpillar [20].…”
Section: End-of-life Managementmentioning
confidence: 99%
“…As illustrated in Figure 2 above, a new state of the art may be defined by establishing an advanced recycling model called Controlled Closed Loop Recycling (CCLR) geared towards 100% material recovery and remanufacturing of automotive polymer parts replacing material of currently non-recyclable parts with polyethylene (PET) or polypropylene (PP) (Kahn, et al 2006).…”
Section: Figure 2: Controlled Closed Loop Recyclingmentioning
confidence: 99%
“…Accordingly, many reported RFID implementation cases have been in this form [16,17]. Foster et al [1] suggested a system architecture for an automotive OEM and suppliers to monitor stillages in real-time bases by attaching active RFID tags on high valued stillages for the seamless part supply.…”
Section: Rfid Applications In Manufacturingmentioning
confidence: 99%